2020
DOI: 10.1002/er.6163
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation analysis of sediment‐microbial fuel cells for energy recovery from microbial activity in soil

Abstract: Summary In natural environments, voltage gradients can be created in soil or sediments from inherent microbial activity. Present work has utilized sediment microbial fuel cell or s‐MFC for dark flocculent surface sediments to see bioelectricity generation potential at Jaipur, Rajasthan in India. Using a glucose rich substrate media and low external resistance, system generated external voltage of around 500 ± 10 mV, with power density peaking after a week of operation with 2122 ± 80 mW/m2 and current density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This is provided that the output is stabilized. Studies have shown that the production of bioelectricity can be improved by changing the electrode material, the distance between the electrodes, allowing heterotrophic microbial growth on the cathode, and through various arrangement mechanisms it is possible to achieve stability (Bose et al, 2021a). These findings were obtained by testing different reactor configurations.…”
Section: Microbial Communities and Its Bioprocessing Structuresmentioning
confidence: 99%
“…This is provided that the output is stabilized. Studies have shown that the production of bioelectricity can be improved by changing the electrode material, the distance between the electrodes, allowing heterotrophic microbial growth on the cathode, and through various arrangement mechanisms it is possible to achieve stability (Bose et al, 2021a). These findings were obtained by testing different reactor configurations.…”
Section: Microbial Communities and Its Bioprocessing Structuresmentioning
confidence: 99%
“…[8] Electrons flow to the cathode through an external circuit and react with protons and electron acceptors to form stable reduction products. [9] The voltage change can be measured intermittently with a voltmeter or continuously collected with an electrochemical workstation. [10] In theory, the principle of electricity generation in MFCs is similar to conventional fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…The exoelectrogens are attached to the anode to form a biofilm, which catalyzes the decomposition of organic matter to release electrons and protons [8] . Electrons flow to the cathode through an external circuit and react with protons and electron acceptors to form stable reduction products [9] . The voltage change can be measured intermittently with a voltmeter or continuously collected with an electrochemical workstation [10] .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Oxygen and nitrate at the cathode become electron acceptors that consume electrons transferred from the anode. [9][10][11] Several factors were identified to contribute to the performance of MET, such as type of electron donor, values of the external resistors, electron transport from the biofilm to the anode electrode, the type of electron acceptor, the efficiency of the cathode electrode performing the reduction process, and high proton transport. 2,12 In a dual-chamber MET, a membrane separates the electrodes to prevent microorganism crossover and oxygen from the cathode to the anode chamber.…”
Section: Introductionmentioning
confidence: 99%